Pengaruh Pendidikan Kesehatan Melalui Metode Ceramah Terhadap Perubahan Perubahan Perilaku Remaja dalam Menghadapi Perubahan Sistem Reproduksi - Maria Putri Sari, Utami (Jurnal Keperawatan Notokusumo, 2013)
Background : teenage period is a period of growth initiated from maturity of reproductive organs. Concern in reproduction system is minimum nowadays. Teenagers often lack basic information about methods of maintaining reproductive health. Objective : The study aimed to identify impact of lecture to behavior the teenagers assessed from knowledge, attitude, and action in responding to changes of reproduction system.